JURIDICAL ANALYSIS OF LAW NO. 42/1999 WITH CONSTITUTIONAL COURT DECISION NO. 18/PUU-XVII/2019 ON MOTOR VEHICLE WITHDRAWAL BY DEFAULTING DEBTORS - Ermita, Yeni; Sumaryanto, Dr. A. Djoko (IUS POSITUM: Journal of Law Theory and Law Enforcement, 2024)
Motor vehicles are often confiscated by people who do not repay debts, and are occasionally subjected to violence or threats from debt collectors. Meanwhile, Law No. 42/1999 Article 15 stipulates that the withdrawal can be self executed. However, Constitutional Court Decision No. 18/PUU-XVII/2019 states that execution must go through the courts, which leads to differences in interpretations. Some interpreted the withdrawal to require a judicial process, while others argued that it could be done on their own, which led to forced withdrawals by debt collectors. Therefore, this research is conducted to  analyze the juridical implications of Law No. 42/1999 on Fiduciary Guarantee regarding the Constitutional Court Decision No. 18/PUU-XVII/2019, which specifically discusses motor vehicle withdrawals by creditors against defaulting debtors. A normative juridical approach with qualitative analysis was chosen to obtain an in-depth and accurate understanding of the legal issues discussed. The approaches used in this research are statute approach and case approach. The result of this research is in Decision No. 18/PUU-XVII/2019, the Constitutional Court reviewed and reinterpreted Article 15 Paragraphs (2) and (3) of Law No. 42/1999 on Fiduciary Guarantee. The Court found that the law allowed for arbitrary actions by creditors, causing injustice to debtors. The decision mandated that the execution of collateral, such as the withdrawal of a motor vehicle, must be done through a District Court decision rather than unilaterally by the creditor.